2007
DOI: 10.1021/es061957q
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigations of Enhanced Sulfate Reduction as a Groundwater Arsenic Remediation Strategy

Abstract: Landfills have the potential to mobilize arsenic via induction of reducing conditions in groundwater and subsequent desorption from or dissolution of arsenic-bearing iron phases. Laboratory incubation experiments were conducted with materials from a landfill where such processes are occurring. These experiments explored the potential for induced sulfate reduction to immobilize dissolved arsenic in situ. The native microbial community at this site reduced sulfate in the presence of added acetate. Acetate respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 37 publications
1
44
0
Order By: Relevance
“…In addition to Farquhar et al (2002) and Wolthers et al (2005b), other experimental studies that examined As sequestration by sulfide minerals include Rittle et al (1995), Castro et al (1999), Jong and Parry (2003), Keimowitz et al (2007). How their results compare to ours is unclear, however, because none of these studies identified the sulfide minerals that formed.…”
Section: Arsenic Sequestration By Iron-sulfide Mineralsmentioning
confidence: 66%
See 1 more Smart Citation
“…In addition to Farquhar et al (2002) and Wolthers et al (2005b), other experimental studies that examined As sequestration by sulfide minerals include Rittle et al (1995), Castro et al (1999), Jong and Parry (2003), Keimowitz et al (2007). How their results compare to ours is unclear, however, because none of these studies identified the sulfide minerals that formed.…”
Section: Arsenic Sequestration By Iron-sulfide Mineralsmentioning
confidence: 66%
“…This observation implies that we may be able to remediate As contamination in situ in reducing aquifers simply by injecting SO 4 2À to stimulate microbial SO 4 2À reduction (Kirk et al, 2004). Other studies have also concluded that enhancing SO 4 2À reduction may be useful for As remediation, including Rittle et al (1995), Castro et al (1999), Jong and Parry (2003), Lee et al (2005), and Saunders et al (2005), Keimowitz et al (2007). In a field test of this strategy at a naturally contaminated site in Bangladesh, Saunders et al (2008) observed a decrease in aqueous As concentration coinciding with stimulated SO 4 2À reduction.…”
Section: Introductionmentioning
confidence: 84%
“…Model 1 has been used in many studies to calculate As speciation in sulfidic waters and it is assumed in all of them that redox processes are controlled by the couple SO 2À 4 /HS À . (O'Day et al, 2004;Bostick et al, 2005;Haque and Johannesson, 2006;Lee et al, 2006;Keimowitz et al, 2007;Beak et al, 2008;Gallegos et al, 2008). The sub-set of reactions describing As sulfidation in Model 2 (reactions 19-45) was provided by Helz and Tossell (2008); these authors critically reviewed As speciation in previous laboratory studies and used an ab initio quantum chemical method to derive a provisional model of As speciation in sulfidic waters.…”
Section: Thermodynamic Modelingmentioning
confidence: 99%
“…For these reasons, sulfidogenesis via microbial SO 4 2À -reduction is widely believed to retard As mobility in reducing subsurface environments. Furthermore, it has been suggested that As-contaminated groundwaters might be remediated by the deliberate in-situ stimulation of SO 4 2À -reducing bacteria (Kirk et al, 2004;Keimowitz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%